DEVELOPMENT OF INTEGRITY CHARACTER EDUCATION GUIDEBOOK BASED ON TRADITIONAL GAMES FOR 10-12 YEAR OLD CHILDREN - Swandewi Ni Kadek; Gregorius Ari Nugrahanta (Universitas Majalengka, 2023)
Moral decadence that occurs in the scope of schools, such as bullying, cheating, plagiarism, corruption, and so on, shows the lack of integrity in school-age children. Awareness of integrity needs to develop from an early age. This study aims to create a traditional game-based integrity character education guidebook and determine the quality and effect of its application on the integrity character of children aged 10-12 years. This research was conducted using the ADDIE-type Research and Development (R&D) method. The data were analyzed qualitatively and quantitatively to identify and describe the impact's significance, magnitude, and effectiveness of the implementation. The researchers involved ten students of SD Negeri Jonggrangan at Jonggrangan, Sendangmulyo, Minggir, Sleman as research subjects. The results of research and development of a traditional game-based integrity character education guidebook based on the five steps of ADDIE show (1) the guidebook consider to have